Protein Digestion-Derived Peptides and the Peripheral Regulation of Food Intake - Caron, Juliette; Domenger, Dorothée; Dhulster, Pascal; Ravallec, Rozenn; Cudennec, Benoit (Frontiers in Endocrinology, 2017)
The gut plays a central role in energy homeostasis. Food intake regulation strongly relies on the gut–brain axis, and numerous studies have pointed out the significant role played by gut hormones released from enteroendocrine cells. It is well known that digestive products of dietary protein possess a high satiating effect compared to carbohydrates and fat. Nevertheless, the processes occurring in the gut during protein digestion involved in the short-term regulation of food intake are still not totally unraveled. This review provides a concise overview of the current data concerning the implication of food-derived peptides in the peripheral regulation of food intake with a focus on the gut hormones cholecystokinin and glucagon-like peptide 1 regulation and the relationship with some aspects of glucose homeostasis.